Tribological and thermal stability study of nanoporous amorphous boron carbide films prepared by pulsed plasma chemical vapor deposition - Liza, S.; Ohtake, N.; Akasaka, H.; Munoz-Guijosa, J.M. (2015)
In this work, the thermal stability and the oxidation and tribological behavior of nanoporous a-BC: H films are studied and compared with those in conventional diamond-like carbon (DLC) films. a-BC: H films were deposited by pulsed plasma chemical vapor deposition using B(CH3)(3) gas as the boron source. A DLC interlayer was used to prevent the a-BC: H film delamination produced by oxidation. Thermal stability of a-BC: H films, with no delamination signs after annealing at 500 degrees C for 1 h, is better than that of the DLC films, which completely disappeared under the same conditions. Tribological test results indicate that the a-BC: H films, even with lower nanoindentation hardness than the DLC films, show an excellent boundary oil lubricated behavior, with lower friction coefficient and reduce the wear rate of counter materials than those on the DLC film. The good materials properties such as low modulus of elasticity and the formation of micropores from the original nanopores during boundary regimes explain this better performance. Results show that porous a-BC: H films may be an alternative for segmented DLC films in applications where severe tribological conditions and complex shapes exist, so surface patterning is unfeasible.